Pengelolaan Pendidik Dan Tenaga Kependidikan Berbasis Budaya Disiplin di SD N Sabranglor Jebres Kota Surakarta - , Parmanto; , Prof. Bambang Sumardjoko, M,Pd; , Dr. Sabar Narimo,MM.,M.Pd (2017)
This study have five aims to describes the characteristics of the planning, organizing, implementing, and monitoring teachers and education personnel based on discipline culture in SD N Sabranglor Jebres of Surakarta City. This research is qualitative research with case study design. Data was collected by observation, interview, and documentation. Data validation was done through continuous observation, data triangulation, and talking with others. Data analysis use Milles and Huberman analysis. Results of this research there are five things about: 1) Planning teachers and education personnel based on discipline culture by drafting a work plan school (RKS) made by the principal, formulate a vision and mission, determine school curricula, conduct program activities in an effort to improve discipline and ability competence and willingness to work, grow the nature of cooperation and harmony, create a sense of open, build a culture of shame, and creative. 2) Organizing teachers and education personnel based on discipline culture is done by preparing teachers in assignments, conduct teacher assignments as needed, perform the division of tasks teachers, and prepare the organizational structure of the school. 3) Implementation of teachers and education personnel based on discipline culture is done by the principal to provide guidance to comply with school rules, act and behave decently, running errands with a full sense of responsibility, carry out the task school on time, and do what is right and fair. School principals guiding teacher who experienced problems make learning device, improve learning in the classroom, and guide teachers and education personnel who violate the rules. 4) Supervision of teachers and education personnel based on discipline culture is done by the principal to oversee passion or motivation of teachers to teach, supervise the attitudes and behavior of teachers and education personnel, punishment and reward.